Design and optimization of lanthanide oxides based catalysts for carbon dioxide methanation - Mat Rosid, Salmiah Jamal (2015)
The Malaysian crude natural gas contains toxic and acidic gases such as carbon dioxide, CO2 (20-30%), and hydrogen sulfide, H2S (0-1%), therefore it should be treated. The current gases treatment process including chemical solvents, adsorption process using hybrid solvents and membrane failed to meet the processing requirement. Instead, catalysts used for the CO2 methanation have been extensively studied and high potential towards converting CO2 gas to methane. In this research, a series of lanthanide oxide based catalysts supported on alumina and doped with manganese and ruthenium were prepared by wetness impregnation method. The lower performance of monometallic and bimetallic oxide catalysts have steered the exploration of trimetallic oxide catalyst. The potential trimetallic oxide catalysts were calcined at 400oC, 700oC, and 1000oC for 5 hours separately. In-home-built micro reactor, Fourier transform infrared (FTIR) spectroscopy and gas chromatography analysis (GC) were used to study the catalytic performance by determining the percentage of CO2 conversion and also the percentage of CH4 formation. From the catalytic screening, it was found that the catalysts with Ru/Mn/Ce (5:35:60)/Al2O3 calcined at 700oC, and Ru/Mn/Sm (5:35:60)/Al2O3 calcined at 1000oC achieved 100% CO2 conversion, Ru/Mn/Pr (5:30:65)/Al2O3 calcined at 800oC achieved 96% CO2 conversion were potential catalysts. The active species in the methanation reaction for each catalyst were MnO2, and RuO2 and CeO2 or Sm2O3 or Pr2O3 respectively. Using two series furnace reactors, all three potential catalysts showed the increasing of CH4 formation. For optimization, the parameters studied were calcination temperatures, based loadings, and catalyst dosage. The optimization was done by using response surface methodology (RSM) with Box-Behnken design which showed the significant parameters and optimum result of cerium with calcination temperature of 697.47oC, based metal ratio of 60.38% and catalyst dosage 6.94 g as suggested by RSM. This result was tested and verified experimentally with difference of only 1%. X-rays diffraction analysis showed that the catalysts imposed an amorphous phase, while field emission scanning electron microscopy illustrated the catalyst surface was covered with small and dispersed particles with undefined shape. From electron dispersive X-rays analysis revealed that there were a reduction of Ru in the used catalyst compared to the fresh catalyst for each potential catalysts. Nitrogen gas adsorption showed that the catalysts were mesoporous structure with type H3 hysteresis loop and Type IV isotherm. Electron spin resonance spectrum showed a free electron interaction due to the presence of the peak for each potential catalyst. Temperature programmed reduction analysis of Ru/Mn/Ce (5:35:60)/Al2O3 catalyst showed more reducible species compared to catalysts containing Sm and Pr due to the presences of more reduce species at lower reduction temperature. The postulated methanation reaction follows the Langmuir Hinselwood mechanism which initially involves adsorption of CO2 and H2 gases on the catalyst surface. For Ru/Mn/Ce (5:35:60)/Al2O3 and Ru/Mn/Sm (5:35:60)/Al2O3 catalysts the product obtained were CH4, CH3OH and H2O. Meanwhile, for Ru/Mn/Pr (5:30:65)/Al2O3 catalyst only CH4 and H2O were observed as a products of the reaction. Lastly, the spent catalysts were successfully regenerated by running under O2 flow at 100oC for 1 hour.